132 Do antibiotics improve the IPOS reported burden of symptoms of pain, breathlessness and confusion?. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Taylor, Lucy; Shah, Sanjay
Abstract : Introduction: The Integrated Palliative Care Outcome Scale (IPOS) offers potential to measure outcomes of palliative care interventions. 1 Antibiotics are commonly given for symptomatic relief in hospices but the evidence base is weak, supported typically from the perceived improvement in symptoms as judged by healthcare professionals. 2–5 IPOS adds the patient's voice to this debate. Methods: A retrospective notes review of 31 inpatients at 2 hospices in Northamptonshire from 20/17/19 to 20/11/19 receiving antibiotics was conducted. The pre and post antibiotic IPOS scores for pain, breathlessness, confusion and 'other' symptoms were analysed using a paired T test facilitated by SPSS V11. Results: The most common use of antibiotics was documented to control 'other' symptoms (n=16) not covered by IPOS. The most common 'other' symptom recorded were fever (n=7), but also included cough, incontinence and drowsiness. Antibiotics caused an average reduction in the IPOS scores for pain of 0.45, CI 1.49 to -1.28 (p 0.11). Breathlessness reduced by 0.16 (CI 1.44 to -0.60, p 0.42). Confusion reduced by 0.26 (CI 1.13 to -0.78, p 0.17). Other symptoms improved by 0.65 (CI -0.11 to -1.18 p 0.02). Conclusion: Although some patients did report improvements, the findings of this audit suggest that antibiotics may not affect patients' IPOS reported symptoms. This prompts reflection on both the use of antibiotics and the implementation of IPOS in the hospices. The potential clinical and research implications of utilising IPOS to evaluate the effectiveness of specific palliative care interventions warrants further research. References: Murtagh FE, Ramsenthaler C, Firth A, Groeneveld EI, Lovell N, Simon ST, Denzel J, Guo P, Bernhardt F, Schildmann, E., van Oorschot B, Hodiamont F, Streitwieser S, Higginson IJ and Bausewein C. 'A brief, patient- and proxy-reported outcome measure in advanced illness: Validity, reliability and responsiveness of the Integrated Palliative care Outcome Scale (IPOS)'. Palliative Medicine 2019;33 (8):pp. 1045–1057. Reinbolt RE, Shenk AM, White PH and Navari RM. 'symptomatic treatment of infections in patients with advanced cancer receiving hospice care'. Journal of Pain and Symptom Management 2005;30 (2):pp. 175–182. Helde-Frankling M, Bergqvist J, Bergman P and Bjorkhem-Bergman L. 'Antibiotic treatment in end-of-life cancer patients. 'A retrospective observational study at a palliative care center in Sweden'. Cancers 2016;8 (9). Nakagawa S, Toya Y, Okamoto Y, Tsuneto S, Goya S, Tanimukai H, Matsuda Y, Ohno Y, Eto H, Tsugane M, Takagi T and Uejima E. 'Can anti-infective drugs improve the infection-related symptoms of patients with cancer during the terminal stages of their lives?'. Journal of Palliative Medicine 2010; 13 (5): pp. 535–540. Rosenberg JH, Albrecht JS, Fromme EK, Noble BN, McGregor JC, Comer AC and Furuno JP. 'Antimicrobial use for symptom management in patients receiving hospice and palliative care: a systematic review'. Journal of palliative medicine 2013; 16 (12): pp. 1568–1574.